Content of cultural urological component in training future teachers philological specialties (Pedagogy of Higher and Secondary Education, 2014)
Mishenina T. M. Content of cultural urological component in training future teachers philological specialties.The paper attempts to establish the content of cultural urological component in training future philologists, which is implemented in educational disciplines cycle of humanitarian and socio-economic training. The essence of the comparative approach to the study of special subjects, which is understood as the examination of phenomena of art (art-graphic, linguistic and literary) within the culture / cultures. The examples of comparative methods in the content of the discipline «Linguistic analysis of the text»"
Keywords: cultural studies component; future teachers’ philological specialties didactic competence; cultural competence; axiological competence comparative approach; axiological competence; comparative approach